Cardiovascular and ventilatory responses to dynamic exercise during epidural anaesthesia in man. - Fernandes, A (1990)
1. In order to evaluate the importance of afferent neural feedback from the working muscles for cardiovascular and ventilatory responses to dynamic exercise, epidural anaesthesia was induced at L3-L4. Six healthy males cycled for 20 min at 57% of maximum oxygen uptake and for 8-12 min at increasing work intensities until exhaustion at 238 +/- 30 W without as well as with epidural anaesthesia. 2. Presence of afferent neural blockade was verified by cutaneous sensory analgesia below T10-T11 and attenuated post-exercise ischaemic pressor response (45 +/- 8-24 +/- 6 mmHg). Efferent sympathetic nerves appear to be intact since basal heart rate and blood pressure as well as the cardiovascular responses to a Valsalva manoeuvre and to a cold pressor test were unchanged. 3. During dynamic exercise with epidural anaesthesia, blood pressure was lower than in control experiments; however, ventilation and heart rate were not affected. 4. The results indicate that afferent neural activity from the working muscles is important for blood pressure regulation during dynamic exercise in man but may not be necessary for eliciting the ventilatory and heart rate responses.